Cryptocurrency as Medium of Exchange and Its Applicability in the Philippine Accounting Standards - Binaluyo, Jonathan P.; Binaluyo, Jonathan P.; Pelo, Justine L.; N. Yumul, Mary Herschelle; . Reyes, Anne Catherine O (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to determine the effects of using cryptocurrency as a medium of exchange in the Philippines and how the existing Philippine Accounting Standards are being applied in terms of reporting and valuation in Financial Statements. The study used qualitative method research to assess the relationship between using of cryptocurrency as a mode of payment today and the possibility of using cryptocurrency as a medium of exchange. The variables of the study are trading values, volatility, data security, and marketability. In trading values, the price of bitcoin varies directly to its volatility. If the volatility of the bitcoin increases, the price of bitcoin also increases. Hence, the value of the virtual currency is greatly affected by trading value. Accounting Standards may not be applicable in this situation unless it is considered to be in Hyper Inflationary Economy. Some countries have issued warnings and amendments while others have expanded their laws regarding virtual currency because one of the crucial features of this is data security. Lastly, in the aspect of marketability, the market capitalization of the virtual currency is growing at an unrealistic rate, to which accounting standards have note identified rules and principles to determine how would this rate are being valued. Different countries have different views with regards to cryptocurrencies. Some consider it as a threat, while others see a potential technology in cryptocurrencies wherein in, various countries made those a legal tender with a specific classification with a corresponding tax rate.